Follow-up strategies in gynecological oncology: searching appropriateness. Issue 6 (1st October 2007) - Zola, P.; Fuso, L.; Mazzola, S.; Gadducci, A.; Landoni, F.; Maggino, T.; Sartori, E.
Abstract : Nowadays, the cost for oncology diseases is growing rapidly, in particular as a consequence of the introduction of new drugs and new diagnostic procedures, and becoming a considerable percentage of the global healthcare expense. On the other hand, a substantial amount of that cost is considered to be imputable to the follow-up procedures. The aim of our paper is to introduce the debate about follow-up policies adopted in gynecological oncology throughout a literature review just based on cost-effectiveness and cost-efficacy in order to explore if the data are consistent with evidences available in this field. Furthermore, it is discussed if common practice fits the needs of patients, gynecological oncologists, and health service. Despite the fact that in gynecological oncology we must consider different clinical situations concerning each specific neoplasm with their peculiar natural history, some general considerations could be drawn in order to set up future initiatives properly